CPAP‐induced mania in bipolar disorder: a case report. (27th August 2013) - Aggarwal, Richa; Baweja, Raman; Saunders, Erika FH; Singareddy, Ravi
Abstract : Objective: In this case report we present our clinical observations of two patients with bipolar disorder with comorbid obstructive sleep apnea (OSA) who were treated with continuous positive airway pressure (CPAP) for their sleep apnea. Background: Bipolar disorder is a psychiatric disorder characterized by the presence of one or more episodes of mania and frequent episodes of depression. This disorder affects approximately 0.8% of the adult population, with estimates from community samples ranging between 0.4% and 1.6%. OSA syndrome is a severe sleep disorder with a prevalence of 2–4% in the general population, the risk of which is increased by obesity. The prevalence of OSA is expected to be high in bipolar disorder due to high comorbid obesity. It is expected that improvement in OSA in patients with bipolar disorder with CPAP will improve mood and other symptoms of bipolar disorder. However, there is a relative lack of data examining this aspect. Results: In both cases of bipolar disorder, CPAP was started after a polysomnographic diagnosis of OSA and CPAP titration study indicating that most of the apneas/hypopneas were eliminated with a significant improvement in oxygen saturation. To our surprise, we noted that in both of these cases initiation of CPAP resulted in manic symptoms. Conclusions: Clinicians need to monitor patients with bipolar disorder closely for worsening of manic symptoms when they are started on CPAP for underlying OSA.